Sex and social media - Tiidenberg, Katrin; Nagel, Emily van der (Emerald Publishing Limited, 2020)
Sex is not only on social media, but social media shapes how we do and think about sex. What practices, norms, anxieties and identities arise when the two intersect? Based on years of research on various sexual social media practices on different platforms Sex and Social Media offers a curious reader an academically informed yet accessible discussion of the nuances of sexual social media and socially mediated sex. The book opens up a much-needed discussion around how social media - as both technology and a corporate service - shapes how we perceive and practice sex today.
Chapter 1. The trifecta of anxieties about sex and social media -- Chapter 2. Social media platforms as the shapers of sex -- Chapter 3. Sexual practices on social media -- Chapter 4. Sex, identities and social media -- Chapter 5. Sex, communities and relationships on social media.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Social media -- Influence; Sex -- Social aspects; Social Science -- Sociology / Marriage & Family; Social interaction